Routledge handbook of migration and development - Bastia, Tanja; Skeldon, Ronald; Routledge (Firm) (New York : Routledge, 2020)
The Routledge Handbook of Migration and Development provides an interdisciplinary, agenda-setting survey of the fields of migration and development, bringing together over60 expert contributors from around the world to chart current and future trends in research on this topic. The links between migration and development can be traced back to the post-war period, if not further, yet it is only in the last 20 years that the 'migration-development nexus' has risen to prominence for academics and policymakers. Starting by mapping the different theoretical approaches to migration and development, this book goes on to present cutting edge research in poverty and inequality, displacement, climate change, health, family, social policy, interventions, and the key challenges surrounding migration and development. While much of the migration literature continues to be dominated by US and British perspectives, this volume includes original contributions from most regions of the world to offer alternative non-Anglophone perspectives. Given the increasing importance of migration in both international development and current affairs, the Routledge Handbook of Migration and Development will be of interest both to policymakers and to students and researchers of geography, development studies, political science, sociology, demography, and development economics.
Part 1. Conceptual perspectives and approaches -- Part 2. Economic and social dimensions: Poverty and inequalities -- Part 3. Families and social policy -- Part 4. Policies, rights and interventions -- Part 5. Key challenges for migration and development -- Part 6. Migration corridors: Large and small -- Part 7. Translating migration and development -- In lieu of a conclusion: Tracing the way forward in migration and development.
OCLC-licensed vendor bibliographic record.
Keywords: Emigration and immigration; Economic development; SOCIAL SCIENCE / Third World Development